On Presence: "Presence" and Myth. - Ankersmit, F. R. (History & Theory, 2006)
There are no dictionary meanings or authoritative discussions of "presence" that fix the significance of this word in a way that ought to be accepted by anybody using it. So we are in the welcome possession of great freedom to maneuver when using the term. In fact, the only feasible requirement for its use is that it should maximally contribute to our understanding of the humanities. When trying to satisfy this requirement I shall relate "presence" to representation. Then I focus on a variant of representation in which the past is allowed to travel to the present as a kind of "stowaway" (Runia), so that the past is literally "present" in historical representation. I appeal to Runia's notion of so-called "parallel processes" for an analysis of this variant of historical representation.